Intelligent Voice-Controlled Robotic Vehicle for Indoor/Outdoor Navigation - Vaibhavi More; Aditi Jadhav; Kaveri Bhalerao; Prachi Ghumare (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This paper presents the design and development of an intelligent voice-controlled robotic vehicle for indoor/outdoor navigation. The proposed system utilizes a combination of speech recognition, artificial intelligence, and robotic navigation to enable users to control the vehicle using voice commands. The vehicle is equipped with a range of sensors, including GPS, lidar, and cameras, to enable autonomous navigation and obstacle avoidance. The system has been tested in various indoor and outdoor environments, demonstrating its ability to accurately respond to voice commands and navigate complex routes. The proposed system has potential applications in areas such as healthcare, transportation, and search and rescue, where voice-controlled robotic vehicles can provide enhanced mobility and assistance.